KETIKA HATI BERUBAH Kajian Teologis tentang Autentisitas Konversi dalam Konteks Ketidakmampuan Mengampuni - Retno Sribertin; Srilia; Yermia (CV. ADIBA AISHA AMIRA, 2026)
True conversion in Christian theology is an essential transformation that must be proven through continuous change of heart and character, not merely an emotional experience or verbal confession. This study examines the theological dimensions of genuine conversion with a focus on forgiveness as an essential indicator of a transformed heart, using a case study of an elder who persisted in bitterness for years following a conflict with a pastor. A qualitative research method with a biblical-systematic theological approach was employed through literature review of biblical texts and systematic theology literature, analyzed descriptively-analytically. The findings show that true conversion includes repentance and faith that produce continuous character transformation, with forgiveness as essential evidence of understanding God's grace. The inability or unwillingness to forgive over the long term indicates a serious disconnect between theological confession and spiritual experiential reality. Prolonged bitterness destroys spiritual life, severs fellowship with God, and defiles many people. This study concludes that the capacity to forgive is a crucial indicator of conversion authenticity, and the church has a pastoral responsibility to lovingly confront bitterness while guiding the congregation toward restoration through forgiveness